Halal Economic Design in the Context of Sustainable Development and Solutions to Environmental Damage - Shochibah Istiqomah; Abdul Mujib; Nikmatul Masruroh (IJIEF: Indonesian Journal of Islamic Economics and Finance, 2024)
The enactment of the Halal Product Assurance Law No. 33 of 2014 on October 17, 2019, has further brought a breath of fresh air to the development of the halal economy in Indonesia. The halal economy is present as an answer to people's concerns regarding various products circulating in the community, starting from the source, process to successfully becoming a product. "Halal" as an icon for several products such as food and beverages, fashion, hotels, cosmetics and medicines, tourism and finance has begun to be echoed in Indonesia. However, until now it has not been able to touch the lowest level of market behavior, namely manufacturers. In the context of sustainable development, "halal" is a form of modern economy, besides that "halal" is an interesting industry to discuss, because currently those who develop the halal industry are not only Islamic countries but also non-Muslim countries are starting to compete, for example America, Brazil, Australia and other countries. In addition, as environmental damage grows due to producers' indifference to externalities, making the halal economy must be present in our lives. The halal economy is currently looking for its design in the midst of the Covid 19 storm that has not yet ended, besides that the halal lifestyle campaign continues to be echoed to get to the Indonesian halal hub 2024. The economic growth in terms of the halal industry must be welcomed with the right design so as not to give the impression that the government imposes certification on its producers. This paper designs the format of the halal economy so that it is easy and can touch the lowest level by using a competitive advantage approach.